Factors Associated with the Implementation of the Covid-19 Transmission Prevention Protocol to Pusdikmin, Lemdiklat, Polri Personnel in Gedebage District, Bandung City in 2022 - Retna Wulan; Hery Prayitno; Putri Puspitasari (Healthy-Mu Journal, 2023)
The trend of increasing a number of indicators of the dangers of the corona outbreak moving in line with the minimal level of community implementation of the implementation of the health protocol. In Pusdikmin itself, there were still 12 personnel aged 18-19 who congregated during recess without wearing masks. When the interview was conducted, there were still 5 people who did not really understand the benefits of implementing prokes. The purpose of this study was to determine the predisposing factors associated with the implementation of the Covid-19 transmission prevention protocol in the personnel of the National Education and Training Center of the National Police in 2022. This study was analytic. Of the 111 respondents, the most respondents were adults (20-60 years old) as many as 61.3%, the most gender was male, namely 63.1%, education was dominated by high school/equivalent as much as 47.3%, personnel knowledge was in good category (87.4%).), as well as the implementation of the Covid-19 prevention protocol in the good category (85.6%). There is a relationship between age, education, and knowledge with the implementation of the protocol for preventing the transmission of Covid-19 on the personnel of the National Education and Training Center for the National Education and Training Center. Meanwhile, gender has nothing to do with the implementation of the protocol to prevent the transmission of Covid-19 on the personnel of the National Education and Training Center for the National Education and Training Center.